A NEW SPECIES OF RAFFLESIA (RAFFLESIACEAE) FROM NORTH SUMATRA - HARRY WIRIADINATA; RISMITA SARI (Research Center for Biology, 2010)
WIRIADINATA, H. & SARI, R. 2010. A new species of Rafflesia (Rafflesiaceae) from North Sumatra. ReinwardtiaÂ 13(2): 95-100. - Rafflesia meijeri Wiriadinata & Sari spec. nov. from North Sumatra is described. It appears closely related to R. rochussenii Teijsm. & Binn. from West Java which has no processes on the disk, smaller flower, the lobes with a different wart pattern, a wider groove with thin lamellae on the central column, ramenta filiform without swollen apex.